(untitled) (Research, Society and Development, 2020)
The objective of this study was to analyze the perception of the recreational care of nursing students enrolled in the optional discipline Ludicoterapia. Study of a qualitative approach, type of action research, carried out with students of the optional discipline Ludicoterapia, graduating in Nursing from a public University in the South of the country. 25 students participated in this study (11 freshmen and 14 veterans). Data collection was performed through a structured questionnaire for situational diagnosis and focus group after completing the course. The data were subjected to thematic analysis of Bardin’s content (pre-analysis, exploration of the material and treatment of the results obtained and interpretation). The research was approved by the Research Ethics Committee. Two categories emerged from the application of the focus group: “The nurse is active in promoting playful care”, with two subcategories: the nurse puts himself in the patient’s place, and the nurse is ethical and true; the second category was “The patient is passive in playful care”, and the subcategory: the patient creates / lives and recreates fantasies through play. The participants narrated that the nurse must be purposeful for playful care, know the context of the patient who is caring, and recognize the precepts such as ethics, respect, secrecy, empathy and that playful care is configured as a link between the nurse and the patient. The participants narrated that play therapy includes touch, affection, affection, listening, empathy, being polite, ethical and true, and they understood that this care relieves the patient’s tensions and suffering.